2020
DOI: 10.1177/1758835920958358
|View full text |Cite
|
Sign up to set email alerts
|

The role of adjuvant chemotherapy in stage I–III male breast cancer: a SEER-based analysis

Abstract: Background and aims: Male breast cancer is an uncommon disease. The benefit of adjuvant chemotherapy in the treatment of male breast cancer patients has not been determined. The aim of this study was to explore the value of adjuvant chemotherapy in men with stage I–III breast cancer, and we hypothesized that some male patients may safely skip adjuvant chemotherapy. Methods: Male breast cancer patients between 2010 and 2015 from the Surveillance Epidemiology and End Results database were included. Univariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…The results showed that 10-year OS rates of patients with lymph node-negative disease and those with lymph node-positive disease were 75% and 43%, respectively, indicating that the death risk of MBC patients with lymph node-positive disease did not decrease significantly after adjuvant chemotherapy 27 . There is another study showing that adjuvant chemotherapy may be skipped for stage I-IIA MBC patients 28 . Additionally, our results also revealed that 4 high-risk patients identified by RI-DR who developed recurrence or deaths might benefit from adjuvant chemotherapy, suggesting that adjuvant chemotherapy may be taken into consideration in MBC patients at high risk of recurrence or metastasis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 10-year OS rates of patients with lymph node-negative disease and those with lymph node-positive disease were 75% and 43%, respectively, indicating that the death risk of MBC patients with lymph node-positive disease did not decrease significantly after adjuvant chemotherapy 27 . There is another study showing that adjuvant chemotherapy may be skipped for stage I-IIA MBC patients 28 . Additionally, our results also revealed that 4 high-risk patients identified by RI-DR who developed recurrence or deaths might benefit from adjuvant chemotherapy, suggesting that adjuvant chemotherapy may be taken into consideration in MBC patients at high risk of recurrence or metastasis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown that chemotherapy can achieve good results in other types of breast cancer. Adjuvant chemotherapy was shown to signi cantly improve OS in a study of MBC [25]. Another study has shown that chemotherapy is a protective factor for prognosis in patients with HER2-positive breast cancer who also have bone metastases [23].…”
Section: Discussionmentioning
confidence: 99%
“…The SEER data browser was used to access all information in the SEER database, which compiled incidence and survival data pertaining to roughly 28% of the US population [ 23 , 24 ]. The SEER-stat software (SEER ∗ Stat 8.3.6) was used to screen the cohort data in the present study.…”
Section: Methodsmentioning
confidence: 99%